Analysis of the Influence of Money Market Experience on Pleasure and Brand Equity for Customers of PT. Pegadaian Malalayang Branch in Manado - Elisabeth Inri Gimon (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
The aim of this research is to explain the influence of money market experience which includes: accessibility, ease of doing business, executional excellence, personalized offering, staff engagement, value for money, and reputation on pleasure and the influence of pleasure on brand equity at PT Pegadaian Malalayang Manado branch. This type of research is quantitative research. Research variables include: accessibility, ease of doing business, executional excellence, personalized offering, staff engagement, value for money, and reputation as independent variables while the dependent BVR is pleasure and brand equity. The total research sample was 150 customers of PT Pegadaian Malalayang Manado branch. The data analysis technique uses multiple linear regression analysis. The findings of this research show that simultaneously, all independent variables influence pleasure, and the pleasure variable influences brand equity. Partial testing shows that there are four hypotheses that have proven their influence on pleasure in the services of PT Pegadaian, Malalayang Manado branch. The four variables are: ease of doing business, executional excellence, staff engagement, and reputation. Meanwhile, three other variables, namely: accessibility, personalized offering, and value for money do not affect pleasure. Pleasure is a variable that has a significant influence on brand equity